SIFAT FISIK DAN MEKANIK ORIENTED STRAND BOARD (OSB) KAYU KARET (Hevea brasiliensis) BERDASARKAN PERLAKUAN PENDAHULUAN DAN KONSENTRASI PEREKAT - Budi, .; Yani, Ahmad; Nurhaida, . (Universitas Tanjungpura, 2018)
The objectives of this research were to know the effect of preliminary treatment, adhesive concentration and the interaction of both factors to physical and mechanical properties of Oriented Strand Board (OSB) of rubber wood that produces the best board that meets JIS A 5908-2003 24-10. The research was conducted at Wood Workshop Laboratory, Wood Processing Laboratory Faculty of Forestry, University of Tanjungpura and Laboratory of PT. Duta Pertiwi Nusantara Pontianak. Materials used in this study were rubber wood, phenol formaldehyde (PF) adhesives and liquid paraffin, with pretreatment (without immersion treatment, cold soaking and heat immersion) and adhesive concentration (6%, 8% and 10%). OSB board was made with the size of 30 cm x 30 cm x 1 cm with a target density of 0,7 gr / cm3 whitewashed phenol formaldehyde adhesive and hot forged with a temperature of 1600 C for 7 minutes. The results showed that preliminary treatment had a very significant effect on the value of thickness development, water absorption, MOE, MOR and stickiness (IB). Treatment of adhesive concentration had a very significant effect on water absorption, adhesive firmness, and strong screw hold. The interaction of these two factors had a significant effect on water absorption and MOE and also had a very significant effect on the value of thickness development and strong screw hold. The best OSB produced in this study was a pre-treated board without immersion with a concentration of 10%, with a density value of 0,7857 gr/cm3, moisture content of 13,4739 %, development of 2-hour thick 1,5772 %, thickness 24 hour 11,1553 %, water absorption 2 hours 10,8460 %, water absorption 24 hours 38,7681 %, MOE 38.000,8885 kg/cm2, MOR 639,0476 kg/cm2, stickiness 18,8454 kg/cm2 and firmly hold the screw 152,4221 kg.Keywords: Adhesive concentration, Oriented strand board, Pretreatment Rubber wood.Â